The Combination of High-Fat Diet and Oral Marijuana Promotes the Development of Fibrosis in the Mouse Corpora Cavernosa. Issue 2 (1st February 2021) - Nguyen, Sabine; Mangubat, Michael; Eleswarapu, Sriram; Wilson, Julian B.; Molina, Jocelyn; Abraham, Andrea; Artaza, Jorge N.; Friedman, Theodore C.; Ferrini, Monica G.
Abstract: Introduction: The link between cannabis use and erectile dysfunction remains unclear. Moreover, the effect of cannabis in tandem with current Western dietary habits is an area in male sexual health that has yet to be explored. This study seeks to investigate the impact of diet and cannabis on penile health in an animal model. Aim: To determine the effects of diet and oral cannabis extract on fibrosis and oxidative stress within the corpora cavernosa of mice. Methods: This is a pilot animal study in which groups of 2-month old C57BL/6J male mice were fed a normal chow diet (NCD) or high-fat diet (HFD) daily and treated with or without either MJ or THC extract for 2 months. After euthanization, mouse penises were isolated and processed for immunohistochemical studies to determine: (i) smooth muscle cell to collagen content, (ii) myofibroblast proliferation, and (iii) anti-oxidative activity. Main Outcome Measures: Quantitative assessment of immunohistochemical markers of fibrosis and oxidative stress within the corpora cavernosa of mice fed a high-fat diet in combination with either oral marijuana (MJ) or Δ-9-tetrahydrocannabinol extract (THC). Results: The combination of HFD with MJ resulted in: (i) a decrease in the smooth/collagen ratio in the corpora cavernosa, (ii) an increase in alpha-smooth muscle actin expression in the tunica albuginea compatible with myofibroblast proliferation, and (iii) a decrease in heme oxygenase 1 expression indicating an increase in oxidative stress. Significant histological changes were not observed in the HFD + THC group. Conclusions: HFD combined with oral MJ extract led to structural alterations in erectile tissue that are associated with accelerated corporal fibrosis. However, the addition of THC to the diet did not exacerbate histological changes within the corpora. Further studies are warranted to elucidate the discrepant effects between MJ and THC in order to optimize the therapeutic potential of cannabis and minimize its adverse effects on penile health.